1970
DOI: 10.1063/1.1659227
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Dynamics and Single-Crystal Constitutive Relations: Shock-Wave Propagation and Precursor Decay

Abstract: Rate-dependent constitutive relations for single crystals are derived in terms of dislocation dynamics. Contributions from slip on the individual glide planes are assumed to superpose linearly to give the total plastic strain. As an application of the theory, equations describing elastic precursor decay are developed for longitudinal plane-wave propagation in fcc, bcc, and rocksalt structures with wave propagation in the [100], [110], and [111] directions. In addition, expressions for precursor decay in zinc (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(53 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Similar analysis on high-deformation of single crystal Cu, 37 other than homogeneous dislocation flow must cause the u fs precursor peak and subsequent stress relaxation. Some possibilities are twinning, shear localization and fracture, or an unconventional dislocation nucleation mechanism to seed the initial density.…”
Section: Rate-dependent Plasticity Modelmentioning
confidence: 96%
“…Similar analysis on high-deformation of single crystal Cu, 37 other than homogeneous dislocation flow must cause the u fs precursor peak and subsequent stress relaxation. Some possibilities are twinning, shear localization and fracture, or an unconventional dislocation nucleation mechanism to seed the initial density.…”
Section: Rate-dependent Plasticity Modelmentioning
confidence: 96%
“…The intensity however is clearly higher than in the case of powder patterns. An explanation for the broaden ing may be the great increase in dislocation density in the elastic wave [18] and the appearance of mosaic structure in the crystal [5]. The increase in tem perature during shock and the corresponding broadening of the reflex can be neglected in the pressure range considered.…”
Section: C) Discussion Of the Resultsmentioning
confidence: 99%
“…Johnson et al (31) proposed constitutive equations describing elastic precursor decay for longitudinal plane-wave propagation in fcc, bcc, and rocksalt structures with the wave propagation in the 100 , 110 , and 111 directions. Calculated theoretical results (Johnson et al [31]) are compared with the experimental data on precursor amplitudes for single-crystal copper (fcc), tungsten (bcc), sodium chloride (NaCl) (rocksalt), and lithium fluoride (LiF) (rocksalt). Asay et al (73) performed experimental studies on shock propagation along a 100 direction in single-crystal LiF and showed that elastic precursor decay is critically dependent on the origin of the sample.…”
Section: Experimental Frameworkmentioning
confidence: 99%
“…In the early 1970s, Johnson et al (31)(32)(33) developed a continuum framework for describing the rate dependent elastic-plastic response of single crystals to shock-wave loading. Their tensor formulation coupled linear elastic response to a dislocation dynamics model that incorporated the appropriate slip system in the shocked crystals.…”
Section: Nonlinear Anisotropic Elastic Incremental Formalismmentioning
confidence: 99%